EFFECT OF INVESTMENT OPPORTUNITY SET (IOS), FIRM SIZE, LIQUIDITY AND LEVERAGE ON EARNING QUALITY IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2014-2019 - Sri Mulyati; Indah Umiyati; Frini Nurtina Dewi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The purpose of this study was to determine the effect of the investment opportunity set (ios), firm size, liquidity and leverage on earnings equity. The independent variable in this study is the investment opportunity set will be measured using the ratio of market value to book value of equity, firm size will be measured using log size, liquidity will be measured using the current ratio, leverage will be measured using the debt ratio and the dependent viariable in this study is earning quality will be measured using the reatio of cash flow from operations to net operating income. This study uses secondary data from the annual financial statement listed on the indonesia stock exchange. The population in this study are property and real estate companies listed on the indonesia stock exchange for the period 2014-2019. Of the 66 companies in the property and real estate category listed on the indonesia stock exchange, there are 35 companies for which all data are available related to the variables used in this research criteria. The method used in this study to determine the research sample is purposive sampling method. The test tool used is using panel data with the help of the eviews 9. The conclusion in this study is that the investment opportunity set, firm size, liquidity and leverage have a positive effect on earning quality. Suggestions for future researchers to add other independent variables that have more influence on earnings quality and use different measurement